Monitoring the quality of training programs for internists and general practitioners - O. M. Drapkina; S. Yu. Astanina; R. N. Shepel (Кардиоваскулярная терапия и профилактика, 2023)
The article considers the problem of monitoring the quality of training programs for internists and general practitioners, conducted during 2020-2022. The aim was to develop a methodology for monitoring the quality of programs implemented by internal medicine departments of universities in subjects of the Russian Federation.Monitoring the quality of educational programs is determined by the compliance of their content with the requirements of professional standards, federal educational standards, healthcare delivery procedures and clinical guidelines. Evaluation of the quality of programs makes it possible to identify promising areas. Targeted methodological recommendations contribute to the development of a unified educational space for the training of internists.